Critical Review of the 2023 Tenth Grade Arabic Textbook for Madrasah Aliyah under Kurikulum Merdeka - Siti Fahimatul llmia; Rizqi Karimatul Khilmi; Cahya Edi Setyawan; Maskanah Maskanah (Universitas Islam Negeri Walisongo Semarang - Indonesia, 2023)
This research aims to examine the Arabic language textbook for Class linguistic appropriateness and graphic appropriateness. This research method uses descriptive qualitative with content analysis methods. The research results indicate this book is suitable because it meets the content, presentation, language, and graphics criteria. The contents of this book are prepared based on the Independent Curriculum Arabic Learning Outcomes (CP) in madrasas. They are equipped with Pancasila Student Profiles and Raḥmatan lil-‘Ālamīn Student Profiles. The presentation is equipped with picture illustrations appropriate to the student's age level of development. The linguistic aspects in this book have met the criteria, but the language used is considered relatively high for tenth-grade students. In terms of graphics, it is in a suitable category because the book meets all the criteria set for textbook printing.